P111 Respiratory Flow Limitation in the absence of Obstructive Sleep Apnoea responds to CPAP therapy. (12th November 2015) - Chakrabarti, B; Emegbo, S; Craig, S; Heseltine, J; Wright, T; Duffy, N; O'Reilly, JF
Abstract : Background: The Apnoea–Hypopnoea index (AHI) is regarded as a gold standard diagnostic marker of Obstructive Sleep Apnoea Syndrome (OSAS). However, a number of patients present with excessive daytime sleepiness (EDS), yet exhibit a raised Respiratory Disturbance Index (RDI), comprising of flow limited breaths in the presence of a normal AHI (<5 events/hr). We sought to evaluate the benefits of CPAP in this "Flow Limitation" cohort compared to a matched population of OSAS subjects. Results: 27 subjects (Mean age 47 (SD 8) years; ESS 17(4); 48% male; BMI 35.60 (8.12)) presented to our Sleep Service with EDS and undertook a cardio-respiratory polysomnograph, demonstrating an RDI >15 and AHI <5 (Mean RDI 16 (4); AHI 3(2); ODI 5(3)) 25 subjects were subsequently treated with CPAP. At "6-week compliance" visits, 20 (80%) were deemed compliant with CPAP (mean nightly usage 6.03 (1.47) hrs; pre-CPAP ESS 18(3) falling to 9 (4) following CPAP. Within the Flow Limitation cohort, statistically significant associations were observed between CPAP compliance and Female gender (100 v 55%), higher BMI (36.61 v 31.56), higher pre-CPAP ESS (18 v13) and lower Pulse Transit Time PTT (300.90 v 316 ms). This "Flow Limitation" cohort was compared with an age/gender matched "OSAS "cohort (ESS 15(5); BMI 38.33 (7.80) AHI 58.16 (25.79) ODI 48 (23)). 26 OSAS subjects were treated with CPAP with 19 (70%) deemed compliant (nightly usage 5.25 (3.55) hrs; pre-CPAP ESS 16 (5) falling to 10(5) following CPAP. Whilst the mean PTT of the OSAS cohort was lower than the "Flow Limitation" cohort, this did not reach statistical significance (298.85(15.04) v 306.44 (18.36) ms; ANOVA; p = 0.1) yet the PTT Deceleration Index (DI), a surrogate of physiological arousal, was significantly higher in the OSAS cohort (59.05(29.33) v 36.32(23.69)/hour; ANOVA; p = 0.003). Conclusion: "Sleepy" subjects exhibiting an elevated Flow Limitation Index in the presence of a normal AHI appear to demonstrate a response to CPAP therapy comparable to that observed in OSAS. Female gender and a higher BMI appear to predict compliance with therapy, whilst the utility of Pulse Transit Time in guiding decision making in "sleepy" subjects with a normal AHI merits further study.